The Effect of the Teams Games Tournament (TGT) Cooperative Learning Model on the Mathematics Learning Outcomes of Fourth-Grade Students at SD Inpres 5 Lolu - Gusti Putu Indra Kurniawan; Zulnuraini Zulnuraini; Nurul Kamisani; Azizah Azizah; Ammar Abdullah Joni Guci (FKIP - Universitas Riau, 2026)
This study aims to analyze the effect of the Teams Games Tournament (TGT) cooperative learning model on the mathematics learning outcomes of fourth-grade students at SD Inpres 5 Lolu, specifically on the topic of fractions. The research used a quantitative approach with a One-Group Pretest–Posttest Design involving 20 students as the experimental sample. Data were obtained through pretest and posttest instruments and analyzed using descriptive statistics, the Shapiro–Wilk normality test, the Paired Sample t-test, and the N-Gain test with the assistance of SPSS Statistics. The results revealed a substantial improvement in students’ cognitive abilities after the application of the TGT model. The average pretest score of 22.5 increased to 81 on the posttest, yielding a mean gain of 58.5 points. The Paired Sample t-test produced a significance value of <0.001, indicating a statistically significant effect of the TGT model on learning outcomes. Furthermore, the N-Gain value of 0.7663 categorized the improvement as high. These findings indicate that the TGT model is effective in enhancing students’ understanding of fractions, increasing engagement, and creating a more interactive learning environment. Thus, TGT can be considered an innovative alternative learning strategy for improving mathematics outcomes at the elementary school level.